Hubungan Dukungan Suami Dengan Kecemasan Ibu Hamil Primigravida Di Kepulauan Waesala - Windatania Mayasari (STIKes Ibnu Sina Ajibarang, 2023)
Pregnancy is physiological state, but the important of pregnancy diagnosis can not be ignored. A little life experience that cause good emotions of great happiness or profound sadness. This research aim to relationship husband support with anxiety of primigravida pregnant at Island Waesala. This research use cross sectional study. The population in this research was pregnant towards delivery . there were 55 responden. Data have taken by primery data, secondary. pregnant with low anciety were 42 (76,4%) and moderate anciety wee 13 (23,6%). Result of statistic chi square test showed that there were role of husband’s support (sig. 0,000). Conclusion Husband Support is relationship to anxiety of primigravida pregnant.